(3LfI GdeQjO Ohf GdeQjOs - (3SjO eMeO Hf SjO GdeNJGQ GdcfJj,J (B1244 (3g` s ((3GdTjN GdHcGi Hf SjOi YHO Gddg Hf GdWGdH s)
(3ChdgG (B:s
(3GdMeO ddg , hfYe Gdehdi , hGdTcQ dg Ydi eG GSHY hChdi hEfg ef YHO ehdGg eMeO Hf GdeNJGQ Hf CMeO Hf CHj HcQ Edi GdehjO GdUGOb SjOi Hf GdeNJGQ , SdGe cGdTeS hVMGgG hHJbQjQ gPG GdefMi jJLg dfG GdcdGe s
(3BNQgG (B:s
(3hba Ydi , hbGd (B: (3eGhdfi Pdc GddhY afGhdJg aCNP jbpQCf hCfG CSeY , adeG bQC GddhM LYd jKfi Ydi GdJCdja abGd (B: (3Seg di Ch GSejg dc , bdJ (B: (3Seg , bGd (B: (3SejJg H` hBNQ OYhGfG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI JGeI eUMMg heQeeg s
(3YdjgG MhGTi s
(3hHYV YHGQGJgG HGdMeQI s
(3bQf GdfSN (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs